Sex-specific prevalence, awareness, treatment and control of hypertension in adults in India: a study for developing sex-specific public policy from the longitudinal ageing study in India (LASI) data 2017-2018 - Ayushi Singh; Priyanka Dixit (BMC, 2023)
Abstract Background and objective Hypertension is a key risk factor for cardiovascular disease and the leading cause of mortality among Indian adults. The difference in health status between men and women is becoming a great burden in itself worldwide. This study aimed to examine the differences between men and women in the prevalence, awareness, treatment, and control of hypertension and related risk factors among people aged 45 and older in India using data from the Longitudinal Ageing Study in India in 2017-2018. Methods Descriptive statistics were presented separately for males and females. Multivariable logistic regression was used to analyze the socio-demographic, lifestyle behaviours, and biological factors associated with the prevalence of hypertension. All statistical analyses were conducted using Stata Version 16.0 statistical software. The study of the data was conducted using survey weights available in the LASI datasets. Key findings Overall, the study found that 45.1% of the study population had hypertension, with 26.9% self-reporting their condition and 30% having hypertension at the time of measurement. Approximately 41% of males and 59% of females had hypertension. The self-reported hypertension of men was found to differ significantly from measured hypertension by 8.7%, while in women the difference was only 1.2%. Diabetes was found to increase the odds of having hypertension in both males (OR = 3.65, 95% CI (3.37-3.97)) and females (OR = 3.46, 95% CI (3.21-3.74)). Conclusion The difference between self-reported and measured hypertension in men and women is contributing to sex-gender and health inequalities that must be addressed. For adult females with hypertension, it is important to prioritize obesity, education level, physical activity, and regular clinic visits to manage chronic conditions. Based on our findings, policy recommendations can be made to focus on increasing women's literacy, promoting men's screening for hypertension, banning tobacco and alcohol sales, and organizing hypertension awareness campaigns specifically for men and in rural areas.